End fixity to spiral strands undergoing cyclic bending - Mohammed Raoof; T.J. Davies (2005)
Based on a semi-empirical approach and guided by the previously reported experimental observations and theoretical work by the first author, it is suggested that for spiral strands with mean axial strains εc > 0.0025 and outside diameters d ≤ 40 mm, plane-section bending may reasonably be assumed in the course of theoretically determining the deflected shape, of the strands in the immediate vicinity of fixed end(s) with the proviso that, at the assumed ideal fixed end(s) to the spiral strands, p/d > 630, where p is the estimated minimum radius of curvature at the fixed end. It is also shown that, in practice, the effective fixed end to the spiral strands undergoing such cyclic bending is located not at the face of the zinc-socketed termination, but well within the socket itself; for an axially preloaded spiral strand of 39mm outside diameter, the effective point of end fixity is shown to be located inside the conical housing, about 60mm (or, say, 1.5 diameters) away from the face of the socket. The practical implications of the present findings as regards the traditional approach(es) for determining the minimum radii of curvature at the theoretically assumed (ideal) fixed end, the exact location of which in practice has invariably not (in the previous literature) been properly defined, are critically discussed with such estimated magnitudes of minimum radii of curvature often used as an input into various available models for design against spiral strand restrained bending fatigue. It is, perhaps, worth mentioning that, in the present terminology, the term 'spiral strand restrained bending fatigue' refers to those cases whereby strand fatigue failures near partially (or fully) restrained terminations of various types occur as a result of cyclic bending of the strand at the termination due to, for example, hydrodynamic or aerodynamic loading.